Galanin antisense oligonucleotides reduce galanin levels in dorsal root ganglia and induce autotomy in rats after axotomy. - Ji, R R (1994)
Antisense (AS) oligonucleotides (ONs) to galanin (GAL) were applied to the proximal end of a transected sciatic nerve, allowing their cellular uptake and transport into injured axons. GAL expression in dorsal root ganglia and self-mutilation behavior (autotomy) were then studied. AS-ONs with phosphorothioate or allyl modifications significantly suppressed the axotomy-induced increase in GAL levels, as demonstrated by immunohistochemistry and exaggerated autotomy behavior, whereas no significant effect on GAL mRNA levels could be demonstrated with in situ hybridization. Allyl-ONs were more effective than phosphorothioate-ONs. An AS-ON with three base mismatches did not induce any of the above effects. These results support the view that the inhibition of axotomy-induced GAL up-regulation is related to autotomy.